Cicero : Speech on Behalf of Publius Sestius. - Kaster, Robert A. (Clarendon ancient history series., 2006)
A new translation of, and commentary on, Cicero's defence of Publius Sestius against a charge of public violence. The speech provides any student of Rome with a fascinating way into the period and is also among the best introductions we have to traditional Republican values and ethics in action. - ;A new translation of, and commentary on, Cicero's defence of Publius Sestius against a charge of public violence. Pro Sestio is arguably the most important of Cicero's political speeches that survive from the nearly two decades separating the Speeches against Catiline and the Second Philippic. Its a.